Antimalarial Potential of Carica papaya and Vernonia amygdalina in Mice Infected with Plasmodium berghei. (29th November 2016) - Okpe, Oche; Habila, Nathan; Ikwebe, Joseph; Upev, Vincent A.; Okoduwa, Stanley I. R.; Isaac, Omiagocho T.
Abstract : The study determined if administration of Vernonia amygdalina and Carica papaya plants provides synergistic effects in ameliorating plasmodium infection in mice. Thirty mice (17.88–25.3 g) were divided into 6 groups of 5 mice each. Group 1 was normal control, while groups 2–6 were intraperitoneally inoculated 2.5 × 10 7 Plasmodium berghei parasitized red blood cell, followed by daily administration of 350 mg/kg aqueous leaf extracts after establishment of infection. Group 2 was disease control, while group 6 was treated with standard drug for four consecutive days. The results showed significant (P < 0.05 ) reduction in percentage of parasite load between the infected treatment groups and disease control group at day 3 after infection, which remained consistent until the end of the experiment. All infected treated groups showed significant (P < 0.05 ) increases in RBC and PCV recovery compared to the disease control, with the exception of WBC. There was insignificant (P > 0.05 ) change in mean body weight of all treated groups except in disease control group. Histological studies of the infected mice indicate recovery of hepatic cells from congested black pigmentation. The reduction in parasite load and recovery of hepatic cell damage/hematological parameters were induced by these plant extracts. This highlighted the important usage of the plant in traditional remedy of malaria infection.